Simulation of the Axially Symmetrical Helical Line - Daškevičius, V.; Skudutis, J.; Štaras, S. (Elektronika ir Elektrotechnika, 2009)
Properties of the axially symmetrical helical line are considered in the paper. Models of systems based on the multi-conductor line method and the CST Microwave Studio software package are used. The expressions for the retardation factor and the input impedance of the system are derived using the multi-conductor line method. Analysis of the retardation factor allowed to show that there are possibilities to design simple axially symmetrical small-size helical systems having good dispersion properties and relatively small characteristic impedance. Simulation made using the CST Microwave Studio package confirmed the properties of the systems revealed using the multi-conductor line method. Synergy of various methods can be effectively used at analysis and design of wide-band periodic structures. Ill. 6, bibl. 10 (in English, summaries in English, Russian and Lithuanian).